PERLINDUNGAN HAK CIPTA ATAS EKSPRESI BUDAYA TRADISIONAL PADA KERAJINAN TANGAN DI PROVINSI KEPULAUAN BANGKA BELITUNG - Nurhaini, Siti (PROGRESIF: Jurnal Hukum, 2017)
This study describes how the copyright protection of traditional cultural expressions on crafts in the province of Bangka Belitung. The study also aimend to determine the role of government on copyright protection of traditional cultural expressions on crafts in the the province of Bangka Belitung. Legal protection of the traditional cultural expressions on the crafts they attempt registration and record-keeping by the government, but there are some traditional cultures are registered and certified by the Ministry of Education and Culture called intangible cultural heritage. The role of government in the protection of copyright in traditional cultural expression in the crafts in this stage is to provide guidance, record keeping and registration by the government. With the government registering traditional cultures in the Pacific Island through the Ministry of Education and Culture annually through several stages of selection by the Ministry Center.